Heart rate variability based sport-specific adaptation process in Paralympic cross-country skiers with visual impairments - Churganov, O. A.; Gavrilova, E. A.; Yakovlev, Y. V.; Tuzlukova, M. D.; Kuznetsov, P. K. (Theory and Practice of Physical Culture, 2019)
Objective of the study was to analyze the heart rate variability (HRV)-based sport-specific adaptation process in cross-country skiing Paralympians with visual impairments. Sampled for the study were elite Paralympic cross-country skiers (n = 42) split up into an Experimental Group (EG, n = 23) of Paralympic athletes with visual impairments and Reference Group (RG, n = 19) of healthy members of the Russian national team. The experiment was designed to test the quiescent-state versus high-intensity-work HRV in pre-season. The analyses and the HR variability data were indicative of the Paralympic EG adaptation to the training workloads claiming higher physiological costs versus the RG, as verified by the significant decline of the quiescent-state functionality economizing function in the EG and the low regulatory system mobilization rates under physical workloads. It was found that the Paralympic athletes` HRV data provide a sound basis for the training process and progress being efficiently customized to the actual individual fitness rates.